SEROPREVALENCE OF HUMAN BRUCELLOSIS AMONG THE HIGH-RISK POPULATION - LAVANYA, K.; SUBHASHINI, B. SRI VANI VIJAYA; KAMALA, P. (International Journal of Current Pharmaceutical Research, 2024)
Objective: Brucellosis is a zoonotic disease of worldwide distribution and has great economic concern. It is a contagious disease of ruminant animals but also effects human beings. The duration of the disease can vary from a few weeks to many months. Methods: A total number of 200 samples tested for RBPT and STAT by using phenol saline as diluent to know the IgG titre and 2-mercaptoethanol was used as diluents to know the IgM titre. ELISA test performed for all positive samples in RBPT, to know the presence of IgM antibody. All the results were analyzed statistically. Results: Of the 200 serum samples, highest proportion of positive cases were slaughter house worker 21.05% distribution according to positivity of RBPT and STST highest proportion in slaughter house workers 13.5% and lowest proportion in PUO cases 6.97%. Conclusion: Prevention of human brucellosis focuses mainly on elimination of infection among farm animals. Cooperation is recommended between public health and veterinary officials to overcome the failure of controlling disease among both animals and humans.